Eight Lucretian Emendations. Issue 1 (1st January 2017) - Butterfield, David
Abstract : Eight conjectures are offered upon the text of Lucretius' De rerum natura (1.912, 3.464, 586, 933, 962, 4.897, 5.888–889 and 6.365).